Laser accessories: surgical fibers, strippers, cleavers, and protective glasses. Issue 3 (7th May 2022) - Keller, Etienne Xavier; Kronenberg, Peter; Tailly, Thomas; Corrales, Mariela; Juliebø-Jones, Patrick; Pietropaolo, Amelia; Somani, Bhaskar; De Coninck, Vincent
Abstract : Purpose of review: This review provides most recent findings and developments relating to surgical laser fibers, strippers, cleavers, and protective glasses. Recent findings: The smallest core diameter that can be used with Holmium:YAG lasers is 200 μm. Smaller core diameter fibers can be used with the Thulium fiber laser and offer better flexibility and lower risk of fracture, at the risk of greater burnback effect. Misleading discrepancies between the true diameter of laser fibers and their packaging labels must be considered. Fiber tip degradation from the burnback occurs within few minutes, thus questioning the need for time-consuming fiber tip reprocessing with fiber strippers and special cleaving tools. This shortcoming also applies to instrument-protecting ball-tip fibers. Cleavage of fiber tips through their protective jackets ('coated tips') is a cheaper alternative for instrument protection, additionally offering better visual control of the fiber tip. Third-generation side-firing greenlight laser fibers are still prone to rapid deterioration. Laser eyewear does not seem necessary for Holmium:YAG applications, whereas laser-specific protective glasses should be worn for greenlight laser applications. Summary: With better understanding of laser accessories, practicing urologists may tailor their practice to reach optimal efficacy and safety for Holmium:YAG, Thulium fiber laser and Greenlight laser applications.